2020
DOI: 10.1242/bio.048108
|View full text |Cite
|
Sign up to set email alerts
|

Nanomorphological and mechanical reconstruction of mesenchymal stem cells during early apoptosis detected by atomic force microscopy

Abstract: statementCellular mechanical damage is connected with the apoptosis of BMSCs, and the alterations in mechanics and nanomorphology may be a sensitive index to detect alterations in cell viability during apoptosis. AbstractStem cell apoptosis exists widely in embryonic development, tissue regeneration, repair, aging and pathophysiology of disease. The molecular mechanism of stem cell apoptosis has been extensively investigated. However, alterations in biomechanics and nanomorphology have rarely been studied.Ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…2), with an overall size of 50 µm for diameter and 13 µm for height (Fig. 2c), which is consistent with the typical size of mesenchymal stem cells [43]. In order to reduce the computational effort and increase the resolution at the same time, only a quarter of the whole cell was modelled.…”
Section: Geometrical Modellingsupporting
confidence: 78%
“…2), with an overall size of 50 µm for diameter and 13 µm for height (Fig. 2c), which is consistent with the typical size of mesenchymal stem cells [43]. In order to reduce the computational effort and increase the resolution at the same time, only a quarter of the whole cell was modelled.…”
Section: Geometrical Modellingsupporting
confidence: 78%
“…At the same time, even at the highest concentrations of CB, the viability of the hASCs was not particularly affected, and after CB's removal from the culture medium, the cells showed a proliferative rate similar to control cells. Some studies demonstrated that CD or CB did not compromise cell proliferation or viability [40,80], but on the contrary, other research reported decreases in both parameters dose-and treatment time-dependently [81][82][83]. In particular, Kocsis and colleagues (2021) showed a great difference in cell viability between MSCs treated with CB for 3 or 24 h, with low (1-8 µM) or high concentrations of this chemical (until 128 µM) [82].…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the CAD tools available in ABAQUS 6.12 ® , the finite element model simulating the nanoindentation process of stem cells was built. The dimensions hypothesized for the model (Figure 1) are the average dimensions typically measured for cells of mesenchymal origin [42]. The subcellular components included in the model were: the nucleus (highlighted in red, Figure 1), the cytoskeleton (highlighted in yellow, Figure 1), and the cell cortex (highlighted in blue, Figure 1).…”
Section: Finite Element Model Of the Nanoindented Mesenchymal Stem Cellmentioning
confidence: 99%